Alunos com deficiência no ensino superior: subsídios para a política de inclusão da UNIMONTES - Oliveira, Antonia Soares Silveira e (Universidade Federal de São Carlos, 2011)
This study starts from our professional concerns in all segments of Basic Education and Higher Education in both Public and Private Institutions. Questions have arisen over the implementation of Inclusive Education, the Quota System and Educational Policy at the State University of Montes Claros - UNIMONTES. To ensure the admission, access and permanence of students with disabilities in higher education go far beyond suitable physical facilities. To establish a policy of inclusion in the University in relation to the disabled is necessary. We cannot deny the social role of UNIMONTES in the North of the State of Minas Gerais and its commitment to provide a more fair and democratic educational process for the production of knowledge and application of inclusion policies that meet the diversity, contributing to social inclusion and human development. In this sense, this research fits into this scenario, whose main axis was to investigate the admission, access and permanence of students with disabilities at the State University of Montes Claros - UNIMONTES admitted through the quota System and also to develop a diagnosis of inclusion policy of this university. In order to identify the study subjects, to examine the documents of COTEC, General Secretary and the Coordination of 27 graduate courses at the institution, within their respective campus Learning Centers based in the city of Montes Claros, was necessary. This analysis revealed then the subjects, who were students who had been admitted by the quota system in Category C (disabled), enrolled in undergraduate courses of this institution in the period of 2005 to 2009. This study was based on the principles of inclusion, that everybody has the right to education, regardless of the difficulties and differences. The research was conducted with the quantitative and descriptive methodology and the data collection instrument were official documents of the institution. The final considerations indicate the need to increase the limited mapping studies of students with disabilities in order to locate them and offer them decent conditions of permanence in the institution, along with institutional actions that will meet their expectations to ensure education for all.
Keywords: Ensino superior; Cotas; Deficiência; Inclusão social; Sistema de cotas; Higher education; Disabilities; Quota system; Social inclusion; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL